Contemporary Political Ideologies - SARGENT, Lyman Tower (The Dorsey Press, 1981)
Explore the full gamut of political ideologies--from democracy to Marxism to political Islam--with CONTEMPORARY POLITICAL IDEOLOGIES: A COMPARATIVE ANALYSIS. Looking objectively at how ideology functions today, you absorb the classics through comparative analysis and delve into the less familiar, yet equally fascinating ideologies of anarchism, fascism, and National Socialism through detailed discussion. You even address some of the most thought-provoking, emerging topics of our day, such as feminism, liberation theology, environmentalism, and terrorism.